2020
DOI: 10.1016/j.echo.2020.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Systolic Function in Patients with Systemic Lupus Erythematosus and Its Association with Cardiovascular Events

Abstract: Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder with potential cardiovascular involvement. The aim of this study was to assess left ventricular (LV) systolic function in a large cohort of patients with SLE using standard echocardiographic measurements and global longitudinal strain (GLS) by two-dimensional speckle-tracking analysis. Furthermore, the association between echocardiographic parameters and the occurrence of cardiovascular events was assessed. Methods: A total of 102 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 34 publications
2
22
2
Order By: Relevance
“…There was no statistically significant difference in terms of LVESV in the three studied groups. Moreover, although SPI reflected left ventricular geometry, there was no significant difference in the three studied groups, indicating that the early left ventricular systolic function may be locally impaired in SLE; however, the decline in function is not obvious, and the overall function is still within the normal range 8 . At the same time, there was a statistically significantly decrease in GLS, GCS and LVtw in the mild‐to‐moderate and severe groups compared to the control group, indicating that the left ventricular systolic function is damaged in the early stage.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…There was no statistically significant difference in terms of LVESV in the three studied groups. Moreover, although SPI reflected left ventricular geometry, there was no significant difference in the three studied groups, indicating that the early left ventricular systolic function may be locally impaired in SLE; however, the decline in function is not obvious, and the overall function is still within the normal range 8 . At the same time, there was a statistically significantly decrease in GLS, GCS and LVtw in the mild‐to‐moderate and severe groups compared to the control group, indicating that the left ventricular systolic function is damaged in the early stage.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, although SPI reflected left ventricular geometry, there was no significant difference in the three studied groups, indicating that the early left ventricular systolic function may be locally impaired in SLE; however, the decline in function is not obvious, and the overall function is still within the normal range. 8 At the same time, there was a statistically significantly decrease in GLS, GCS and LVtw in the mild-to-moderate and severe groups compared to the control group, indicating that the left ventricular systolic function is damaged in the early stage. This may be due to fact that SLE can lead to the deposition of immune complexes in the cardiovascular system or inflammatory changes after complement activation that result in the degeneration of collagen fibers in the myocardial interstitium.…”
Section: Discussionmentioning
confidence: 84%
“…This study showed that LVEF in the SLE group decreased significantly, LVEDV, LV EDmass, and LV ESmass increased significantly, and LVESV had no significant change compared with the control group. Moreover, although SPI reflected left ventricular geometry, there was no significant difference, indicating that the early left ventricular systolic function may be locally impaired in SLE; however, the decline in function is not obvious, and the overall function is still within the normal range [8] . At the same time, the results showed that the three-dimensional strain parameters of the left ventricle (GLS, GCS, and LVtw) decreased in the SLE group, indicating that the left ventricular systolic function is damaged in the early stage.…”
Section: Repeatability Test Of 3d-sti-related Parametersmentioning
confidence: 85%
“…A previous study showed (12) that LV whole strain can evaluate LV systolic function of patients with SLE and found that GLSglobal was reduced in patients with SLE. We obtained the same result.…”
Section: Effect Of LV Layer Myocardial Strain In Patients With Slementioning
confidence: 99%